STANCE OF APPROBATION AND GENEROSITY MAXIMS: A CASE STUDY OF A RURAL-BASED COMMUNITY - Nephawe, Farisani Thomas (E-Journal of Cultural Studies; Vol 17 No 4 (2024): Volume 17 Number 4 November 2024DO - 10.24843/cs.2024.v17.i04.p04, 2024)
The politeness maxims have been sustaining peace and harmony among rural communities from times immemorial by minimising the expression of praise of self and maximising the expression of dispraise of self. Nevertheless, the current philosophies of life surreptitiously devalue their social practice. This study investigated approbation and generosity maxims as the behavioural and cultural perspectives that build holistic narrative descriptions among the rural community. Grounded by Leech’s politeness principle and Wenger’s communities of practice, the study adopted the ethnographic qualitative approach. The study population comprised seven purposively selected rural community members and three traditional Vhangona leaders. Data were collected using formal and informal semi-structured interviews for over a year. Two informants participated in the investigation to ensure accurate data collection. A thematic analysis was employed to identify patterns, create codes, and arrange thematically. The preliminary investigation on five rural community members and one traditional chief found that some community members despised approbation and generosity maxims. Nonetheless, after applying a ‘foot-in-the-door’ technique, most community members cherished these maxims exceptionally.’ The implication of this study promotes observation of approbation and generosity maxims. The study argues for incessant resoluteness and resilience in this regard. Keywords : Approbation; generosity; rural-based communities, traditional chiefs